Profiling the low-beta characteristics of the subthalamic nucleus in early- and late-onset Parkinson’s disease - Wu, Delong; Zhao, Baotian; Xie, Hutao; Xu, Yichen; Yin, Zixiao; Bai, Yutong; Fan, Houyou; Zhang, Quan; Liu, Defeng; Hu, Tianqi; Jiang, Yin; An, Qi; et al. (Frontiers in Aging Neuroscience, 2023)
Objectives: Low beta oscillation (13–20 Hz) has rarely been studied in patients with early-onset Parkinson’s disease (EOPD, age of onset ≤50 years). We aimed to explore the characteristics of low beta oscillation in the subthalamic nucleus (STN) of patients with EOPD and investigate the differences between EOPD and late-onset Parkinson’s disease (LOPD). Methods: We enrolled 31 EOPD and 31 LOPD patients, who were matched using propensity score matching. Patients underwent bilateral STN deep brain stimulation (DBS). Local field potentials were recorded using intraoperative microelectrode recording. We analyzed the low beta band parameters, including aperiodic/periodic components, beta burst, and phase-amplitude coupling. We compared low beta band activity between EOPD and LOPD. Correlation analyses were performed between the low beta parameters and clinical assessment results for each group. Results: We found that the EOPD group had lower aperiodic parameters, including offset (p = 0.010) and exponent (p = 0.047). Low beta burst analysis showed that EOPD patients had significantly higher average burst amplitude (p = 0.016) and longer average burst duration (p = 0.011). Furthermore, EOPD had higher proportion of long burst (500–650 ms, p = 0.008) while LOPD had higher proportion of short burst (200-350 ms, p = 0.007). There was a significant difference in phase-amplitude coupling values between low beta phase and fast high frequency oscillation (300–460 Hz) amplitude (p = 0.019). Conclusions: We found that low beta activity in the STN of patients with EOPD had characteristics that varied when compared with LOPD, and provided electrophysiological evidence for different pathological mechanisms between the two types of PD. These differences need to be considered when applying adaptive DBS on patients of different ages.